(untitled) - Porter, Michael E. (New York, 1980)
Competitive Strategy is the definitive work on the subject of "competitive strategy," the hottest new concept in American business today. The book addresses major questions of vital concern to managers, and presents a comprehensive set of analytical techniques for understanding a business and the behavior of its competitors
Keywords: Cạnh tranh,Competition,Quản trị sản xuất công nghiệp,Industrial management